Pengaruh Influencer Gaming dan E-Wom Terhadap Minat Beli Item Game Online Roblox di Bogor - Keisha Aurelia Putri Ayu Widiyanto; Leny Muniroh; Nora Azmia (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the influence of Gaming Influencers and Electronic Word of Mouth (e-WOM) on Purchase Intention of Roblox online game items in Bogor and examine the mediating role of e-WOM. The study employed a quantitative approach using a survey method involving 100 Roblox users residing in Bogor. Respondents were selected through purposive sampling, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that Gaming Influencers have a positive and significant effect on Purchase Intention with a T-Statistics value of 2.035 and a P-Value of 0.042. e-WOM also has a positive and significant effect on Purchase Intention with a T-Statistics value of 5.536 and a P-Value of 0.000. Furthermore, Gaming Influencers significantly influence Purchase Intention through e-WOM as a mediating variable, evidenced by a T-Statistics value of 4.586 and a P-Value of 0.000. The findings reveal that e-WOM is a more dominant factor in influencing purchase intention compared to Gaming Influencers. These results suggest that consumer reviews, recommendations, and online discussions play a crucial role in shaping purchase intentions toward Roblox virtual items.